2022
DOI: 10.3390/ijerph19052878
|View full text |Cite
|
Sign up to set email alerts
|

PM-Bound Polycyclic Aromatic Hydrocarbons and Nitro-Polycyclic Aromatic Hydrocarbons in the Ambient Air of Vladivostok: Seasonal Variation, Sources, Health Risk Assessment and Long-Term Variability

Abstract: Total suspended particles (TSP) were collected in Vladivostok, Russia, which is a typical port city. This study investigated the concentration, potential sources, and long-term variation in particle PAHs and NPAHs in the atmosphere of Vladivostok. The PAH and NPAH concentrations were higher in winter than in summer (PAHs: winter: 18.6 ± 9.80 ng/m3 summer: 0.54 ± 0.21 ng/m3; NPAHs: winter: 143 ± 81.5 pg/m3 summer: 143 ± 81.5 pg/m3). The diagnostic ratios showed that PAHs and NPAHs mainly came from vehicle emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
1
2
0
2
Order By: Relevance
“…This is presumably because they do not capture exactly the same air mass due to the shift in wind direction and the slight deviation in the sampling period. As observed in previous studies, PAH concentrations were higher in winter and lower in summer [19,22,23]. The reasons for the high PAH concentration in winter at this study area according to the previous report are (1) an increase in the burning of coal and biomass for thermal heating, especially in the cold northern parts of China; (2) the prevailing winter wind from the northwest from the stable atmospheric pressure chart pattern; (3) a lower altitude for mixing of atmospheric zones in winter; (4) a decreased decomposition of chemical substances due to low temperatures and weak sunshine in winter; and (5) less breakthrough of PAHs with high vapor pressure from the particulate phase to the gas phase due to low temperatures [19].…”
Section: Behaviors In Pah Concentrations and Their Causessupporting
confidence: 85%
“…This is presumably because they do not capture exactly the same air mass due to the shift in wind direction and the slight deviation in the sampling period. As observed in previous studies, PAH concentrations were higher in winter and lower in summer [19,22,23]. The reasons for the high PAH concentration in winter at this study area according to the previous report are (1) an increase in the burning of coal and biomass for thermal heating, especially in the cold northern parts of China; (2) the prevailing winter wind from the northwest from the stable atmospheric pressure chart pattern; (3) a lower altitude for mixing of atmospheric zones in winter; (4) a decreased decomposition of chemical substances due to low temperatures and weak sunshine in winter; and (5) less breakthrough of PAHs with high vapor pressure from the particulate phase to the gas phase due to low temperatures [19].…”
Section: Behaviors In Pah Concentrations and Their Causessupporting
confidence: 85%
“…To be specific to the source apportionment results, there have been no publications related to the source analyses on PM 2.5 bound PAHs in the study city over the past decade. Only three studies have reported on the levels of PM 2.5 bound PAHs in the ambient atmosphere (L. Feng et al., 2015 ; C. Wang & Cui, 2020 ; Y. Wang et al., 2019 ). These data allow for a longitudinal comparison with our study on the levels of total PAHs (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only three studies have reported on the levels of PM 2.5 bound PAHs in the ambient atmosphere (L. C. Wang & Cui, 2020;Y. Wang et al, 2019).…”
Section: Tablementioning
confidence: 99%
“…Причинами этого, по-нашему мнению, является ряд факторов. Загрязнение воздушной среды города Владивостока обусловлено, в основном, большим количеством автотранспорта (> 500 автомобилей на 1000 жителей) и высокой интенсивностью движения (2500-3000 авт./час) [5,[12][13][14]. Проезжая часть улиц сокращается вследствие парковки автомобилей на дорогах, что затрудняет движение, соз- даёт «пробки» и способствует увеличению загазованности воздуха.…”
Section: результаты исследования и их обсуждениеunclassified
“…Проезжая часть улиц сокращается вследствие парковки автомобилей на дорогах, что затрудняет движение, соз- даёт «пробки» и способствует увеличению загазованности воздуха. Кроме того, значительный вклад в загрязнение воздуха вносит использование низкокачественного топлива на предприятиях, выбросы технически устаревших производственных объектов, условия муссонного климата с характерными сезонными направлениями ветра, расчлененным рельефом, высокой повторяемостью приземных, приподнятых инверсий и слабыми скоростями ветра [5,[12][13][14].…”
Section: результаты исследования и их обсуждениеunclassified